Recent advance in polyolefin nanocomposite - Li, Yongmei. (2010)
Polyolefin materials are the most widely used industrial material, like packing and piping. To order to apply polyolefin materials in construction and automobile industry, their mechanical properties shall be improved. In this project, extremely strong materials, Carbon nanotube and clay are added to polyethylene matrix separately with different concentrations. For polyethylene and carbon nanotube system, the thermo properties were studied by thermogravimetry analysis and differential scanning calorimetry. The mechanical properties, like young’s modulus, tensile strength and ultimate strain were also analyzed. In addition, the effects of carbon nanotube concentration on thermo stability and mechanical properties were studied. For polyethylene and clay system, three types of modified clay were used to improve the miscibility of PE and Clay, and the thermo properties and mechanical properties were studied.